2015
DOI: 10.3329/ralf.v2i2.25000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability for grain yield and yield associated traits in transplant Aman rice (Oryza sativa L.)

Abstract: For any crop improvement program, it is imperative to assess the grain yield progress of the existing crop varieties to find the further avenue to out yield the existing superior ones. Therefore, an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from July to December 2013 to find out the genetic variation for grain yield and their associated traits of transplant Aman rice varieties. The experiment consisted of 11 varieties viz. Bashiraj, Binadhan-7, BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several reports have also been published on significant phenotypic variation among rice accessions although evaluated in only one environment [42][43][44]. Islam et al [45] observed highly significant genetic variability in 113 rice genotypes for 18 traits studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have also been published on significant phenotypic variation among rice accessions although evaluated in only one environment [42][43][44]. Islam et al [45] observed highly significant genetic variability in 113 rice genotypes for 18 traits studied.…”
Section: Discussionmentioning
confidence: 99%